The four biggest malware threats to UK businesses. Issue 3 (March 2020) - Reynolds, Roy
Abstract : It's official – cyber criminals are steadily switching their focus from consumers to organisations, with global business malware detection rates up 13% during 2019, and no sign this trend will slow during 2020. Cyber criminals are switching their focus from consumers to organisations, with business malware detection rates up 13% during 2019 and no sign this trend will slow down. Attackers are increasingly bold about the ways they monetise the information they steal. And the UK retains the unenviable honour of being the cybercrime epicentre of Europe, with the UK service sector the most-targeted industry, followed by education, retail and manufacturing. Roy Reynolds of Vodat examines the four biggest malware threats for UK businesses, how they can infect your digital networks and the steps necessary to remain malware-free.